2006
DOI: 10.1128/ec.00057-06
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Siderophore Ferricrocin Is Involved in Iron Storage, Oxidative-Stress Resistance, Germination, and Sexual Development in Aspergillus nidulans

Abstract: Iron is required by most organisms, but an excess of this metal is potentially toxic. Consequently, uptake and intracellular storage of iron are tightly controlled. The filamentous fungus A. nidulans lacks the iron storage compound ferritin but possesses an intracellular siderophore, which is accumulated in a highly regulated manner as iron-free desferri-ferricrocin or iron-containing ferricrocin via transcriptional regulation of the nonribosomal peptide synthetase SidC. Biosynthesis of desferri-ferricrocin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 36 publications
6
99
1
Order By: Relevance
“…Asexual spores of an A. nidulans ⌬sidC strain show hypersensitivity to ROS more clearly than mycelia (13). In our experiments, no significant difference in sensitivity to ROS was observed between WT and ⌬nps2 strains of C. heterostrophus during vegetative growth (see Fig.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Asexual spores of an A. nidulans ⌬sidC strain show hypersensitivity to ROS more clearly than mycelia (13). In our experiments, no significant difference in sensitivity to ROS was observed between WT and ⌬nps2 strains of C. heterostrophus during vegetative growth (see Fig.…”
Section: Discussionmentioning
confidence: 43%
“…Application of ferricrocin fully restored WT fertility to the G. zeae ⌬nps2 strain. Recently, Eisendle et al (13) reported that a ⌬sidC strain is impaired in sexual development in the homothallic ascomycete A. nidulans. Application of ferricrocin restored the ability of the ⌬sidC strain to undergo WT sexual development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three pairs were identified. SNOG_02134.2 was linked to NPS2, and both appear to be orthologous to the Aspergillus nidulans gene SidC (Eisendle et al, 2003), which is responsible for the synthesis of ferricrocin, an intracellular iron storage and transport compound involved in protection against iron toxicity (Eisendle et al, 2006). It is likely that SNOG_02134.2 and NPS2 play similar roles.…”
Section: Functional Analysis Of Proteinsmentioning
confidence: 99%
“…fumigatus produces two major hydroxamate-type siderophores: the fusarinine desferri-triacetylfusarinine C (DFTafC) is excreted to mobilize extracellular iron, and the ferrichrome desferri-ferricrocin (DF-FC) is employed for intracellular iron storage (4,5,7,16,27). Production of both siderophores is up-regulated by iron starvation, and the A. fumigatus siderophore production resembles that of Aspergillus nidulans (16,27).…”
mentioning
confidence: 99%